2022
DOI: 10.3389/fonc.2022.811183
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ophiopogonin C in Ameliorating Radiation-Induced Pulmonary Fibrosis in C57BL/6 Mice: An Update Study

Abstract: BackgroundThe aim of this study was to assess and update the protective effects and underlying mechanisms of Ophiopogonin C (OP-C), a biologically active component separated and purified from Ophiopogon japonicus, in ameliorating radiation-induced pulmonary fibrosis in C57BL/6 mice administered thoracic radiation.Methods and MaterialsWe randomly divided 75 mice into five groups and administered a dose of 12-Gy whole thoracic radiation to establish a pulmonary fibrosis animal model. Mice were treated with OP-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…In its ESI-MS/MS spectrum, the product-ion at m/z 575 ([M − H − Rha] − ) indicated the presence of the Rha group. According to the literature [21][22][23], there was a Glc group in ophiopogonin C ′ , while NLF of 162 Da was not observed in this experiment. This observation indicated that the Glc group should be directly attached to the core structure, and Rha was attached to the Glc.…”
Section: The Characteristic Fragmentation Mechanism Of Type-i Steroid...mentioning
confidence: 42%
See 3 more Smart Citations
“…In its ESI-MS/MS spectrum, the product-ion at m/z 575 ([M − H − Rha] − ) indicated the presence of the Rha group. According to the literature [21][22][23], there was a Glc group in ophiopogonin C ′ , while NLF of 162 Da was not observed in this experiment. This observation indicated that the Glc group should be directly attached to the core structure, and Rha was attached to the Glc.…”
Section: The Characteristic Fragmentation Mechanism Of Type-i Steroid...mentioning
confidence: 42%
“…MS 2 [911]: 869(100), 851(58), 737 (21), 779 (10), 723 (8), 652 (6), 719( 6) MS 2 [927]: 885(100), 867(54), 753 (16), 885 (13), 735 (7), 739 (5), 721 (37), 903 (32), 933 (31), 753 (15), 1061 (13), 899 (12), 591(8) (30), 903 (32), 933 (31), 753 (15), 1061 (13), 899 (12), 591 (39), 949 (26), 787 (22), 1077 (15), 769 (15), 915 (13), 607 (10) Hydroxyl-Ophiopogonin J/Ophiopogonin (11), 1033 (9), 1015 (7), 1063 (5), 883(3), 899(1)…”
Section: Detection and Structural Elucidation Of Or Steroidal Saponinsunclassified
See 2 more Smart Citations
“…Furthermore, ophiopogonin C can reduce collagen deposition and the accumulation of inflammatory cells and fibroblasts in mice with PF, decrease the levels of pro-fibrotic cytokine TGF-β1, and increase SOD activity in lung tissue. These effects ultimately alleviate mortality and fibrosis levels in mice ( Fu et al, 2022 ).…”
Section: Pharmacological Study Of Mmdd In Pf Treatmentmentioning
confidence: 99%